Entrepreneurial Narrative in Building a Creative Business Ecosystem: A Qualitative Study - Sharon Kumaratih Dewi Wardoyo; Abraham Leslie Petir Lelengboto (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study aims to develop an understanding of Jeffrey Jouw’s (Jejouw) entrepreneurial journey in establishing USS Network as a business ecosystem within the creative industry through a narrative analysis approach. The research adopts a qualitative method, using data from YouTube podcast episodes, with verbatim interview transcripts as the primary data. Opportunity-driven entrepreneurship and effectuation theory are used as conceptual and theoretical frameworks. The findings reveal that Jejouw’s decision to become an entrepreneur was driven by both recognized and unrecognized opportunities shaped by early family experiences, as well as a conscious initiative to start a small-scale business. His entrepreneurial journey aligns closely with the dimensions of effectuation theory, namely bird-in-hand, affordable loss, crazy quilt, lemonade, and pilot-in-the-plane.